Neogene exhumation and relief evolution in the eastern Betics (SE Spain): Insights from the Sierra de Gador. (1st February 2017) - Janowski, Marianne; Loget, Nicolas; Gautheron, Cécile; Barbarand, Jocelyn; Bellahsen, Nicolas; Van Den Driessche, Jean; Babault, Julien; Meyer, Bertrand
Abstract: The Betics are a key area to study an orogenic landscape disrupted by late‐orogenic extension. New low‐temperature thermochronology (LTT) data (AHe and AFT) coupled with geomorphic constraints in the Sierra de Gador (Alpujarride complex) are used to reconstruct the cooling history and evolution of relief during the Neogene. We document three stages: (1) a fast cooling event between 23 and 16 Ma associated with the well‐known extensive tectonic exhumation of the Alpujarride unit, (2) a period of slow cooling between 16 and 7.2 Ma related to a planation event and (3) a post‐7.2 Ma surface uplift associated with the inversion of the Alboran domain undetected by LTT. The planation event followed by this late uplift can explain the occurrence of inherited low‐relief surfaces overlain by Tortonian–Messinian platform deposits at the top of the range. Finally, we propose that the Sierra de Gador is a more transient landscape than the nearby Sierra Nevada.